Enhancement of Physical Learning Results in Subject Matter of Dynamic Electricity through Problem Based Learning Methods on IX-B Grade Students at SMPN 3 Surabaya - Setiyono, Luhur (SAINTIS Publishing, 2019)
Physics learning in teaching and learning activities are known not doing interaction between students and their teachers, causing learning outcomes to be not maximal. This research aims to enhancement of physical learning results of dynamic electrical materials through problem based learning methods on IX B grade students at SMPN 3 Surabaya. The design of this research is Classroom Action Research which is carried out in two cycles with 4 stages which are planning, action, observation and reflection. The first and second cycles discuss the subject matter of dynamic electricity. The subject of this research is 38 students of IX B grade students at SMPN 3 Surabaya. The main of data collection technique used tests and observations, while supporting techniques used documentation. The results of the research show that there was an increase from cycle 1 to cycle 2. The average value of student learning outcomes in cycle 1 reached 73.42 and in cycle 2 it increased to 86.57. The classical completeness percentage of student learning outcomes in the first cycle reached 65.79% and in the second cycle increased 21.05% to 86.84%.Based on the results of the above research, it can be concluded that there is an increase in student learning outcomes after the application of the problem based learning model on subject matter of dynamic electricity on IX B grade students of SMPN 3 Surabaya, so problem based learning models can be used as alternative learning models in an effort to improve outcomes good learning.